Flexible Lifestyles for Youth (FL3X) behavioural intervention for at‐risk adolescents with Type 1 diabetes: a randomized pilot and feasibility trial. Issue 6 (30th December 2014) - Mayer‐Davis, E. J.; Seid, M.; Crandell, J.; Dolan, L.; Lagarde, W. H.; Letourneau, L.; Maahs, D. M.; Marcovina, S.; Nachreiner, J.; Standiford, D.; Thomas, J.; Wysocki, T.
Abstract Aim To determine the potential effect sizes for the Flexible Lifestyle for Youth (FL3X) behavioural intervention to improve glycaemic control (HbA1c) and quality of life for at‐risk adolescents with Type 1 diabetes. Methods Participants [n = 61; age 12–16 years, HbA1c 64–119 mmol/mol (8–13%)] were randomized to FL3X (minimum three sessions) or usual care. Effect sizes (Cohen's d), comparing the mean difference between the groups, were calculated. Results Study retention (95%), attendance at intervention sessions (87% attended all three sessions) and acceptability were high (100% of the adolescents and 91% of parents would recommend the programme to others). Overall, 41% of participants in the intervention group and 24% of participants in the control group were 'responders' [HbA1c decreased by > 6 mmol/mol (0.5%); d = 0.37]. HbA1c levels decreased (d = ‐0.18), diabetes‐specific quality of life increased (d = 0.29), but generic quality of life decreased (d = ‐0.23) in the intervention compared with the control group. Conclusions The FL3X programme merits further study for improving HbA1c and diabetes‐specific quality of life in adolescents with Type 1 diabetes. (Clinical trials registry no.: NCT01286350).